Immediate outcomes of pancreatoduodenalectomy in multivisceral surgery with vascular resection - V. I. Egorov; A. G. Kotelnikov; Yu. I. Patyutko; F. Sh. Akhmetzyanov; A. N. Polyakov; N. E. Kudashkin; D. V. Podluzhny (Сибирский онкологический журнал)
Purpose: to study the immediate outcomes of pancreaticoduodenalectomy (PD) in multivisceral surgeries (MVS) with vascular resections. Material and Methods. The study included 145 patients who underwent pancreaticoduodenalectomy with resection of the major vessels, including the superior mesenteric vein, the portal vein, and the inferior vena cava. These patients were divided into two groups. The main group included 32 patients who underwent MVS with PD, and the control group consisted of 113 patients who underwent PD. Results. There were no statistically significant differences in the immediate outcomes between two groups. Pancreatic fistula developed more often in the MVS with PD group than in the PD group (25 vs 11.5 %, p=0.055). The incidence of resected vein thrombosis in the main group was 9.4 %, in the control group was 1.8 % (p=0.07). Postoperative intra-abdominal bleeding was 6.2 % vs 8 % (p=1.0). Postoperative mortality was 6.2 % in the MVS with PD group and 8.8 % in the PD group (p=1.0). True vascular invasion was confirmed by pathomorphological examination in 20 (64.5 %) cases in the MVS with PD group and in 81 (71.7 %) cases in the PD group (p=0.44). Conclusion. Although no statistically significant differences were observed between the two groups, venous resections in multivisceral surgeries involving pancreaticoduodenalectomy demonstrated a higher incidence of pancreatodigestive anastomosis complications and a higher frequency of venous thrombosis compared to pancreaticoduodenalectomy without resection of adjacent organs, which must be taken into account when planning surgery and managing the postoperative period of this category of patients.